KOMPETENSI PROFESIONAL, DAN SUPERVISI PENDIDIKAN SERTA DISIPLIN KERJA DALAM MEMPENGARUHI KINERJA GURU SMP NEGERI 1 BUMIAGUNG WAYKANAN LAMPUNG - Ripda Erwin; Winda Feriyana (Jurnal AKTUAL, 2019)
The aim of this study was to determine the effect of proffesional competence, education supervision and work discipline to the performance of teachers Junior High School 1Bumiagung Waykanan Lampung. The problems of this study whether there are Junior High School 1 Bumiagung Waykanan Lampung. The data used in this study are primary data 30 respondent reply. Models  analysis used multiple linear regresion and by testing the validity and reliability of instruments. Test charactistics data that is test of normality and linearity test. Test model consist of multicolinearity test and heterokesdatisitas test. Multiple linear regresion test result showed positive proffesional competence, education supervision and job discipline to the performance of teachers Junior High School 1Bumiagung Waykanan Lampung. This study indicates conformity with the theory of proffesionalis competence, education supervision and job discipline of teachers and also performance. Also there are compatibility with previous studies. Increased proffesional, education supervision and job discipline also improve the performance of teachers.